MiR-346 functions as a pro-survival factor under ER stress by activating mitophagy. (28th January 2018) - Guo, Junfei; Yang, Zhen; Yang, Xi; Li, Tong; Liu, Min; Tang, Hua
Abstract: Stress in the endoplasmic reticulum (ER) triggers the unfolded protein response (UPR), which attempts to restore normal function of the ER. Both autophagy and miRNAs have been reported to participate in the process of ER stress, but the relationship between these two factors is still obscure. In this study, we demonstrated that miR-346, which was induced under ER stress, modulated autophagic flux in HeLa cells. By regulating the process of autophagy, miR-346 reduced the ROS level in the cells, thus protecting them from death following ER stress. Furthermore, we demonstrated that GSK3B was the target of miR-346 and participated in ER stress-related autophagy. miR-346 activated autophagy by interrupting the association between BCL2 and BECN1 in a GSK3B-dependent manner. Our findings shed new light on the role of miRNAs during ER stress and suggest a new mechanism for the induction of autophagy under ER stress. Highlights: We first demonstrated the role of miR-346 in ER-stress induced autophagy. miR-346 modulated ROS level in the cell via promoting mitophagy under ER-stress. miR-346 positively regulated the expression of GSK3B. miR-346 modulated the ubiquitination of BCL2 via GSK3B dependent manner.